The Development of Interactive Learning Media Based on Articulate Storyline 3 on Thermochemistry to Enhance Student's Conceptual Understanding - Faiza Ulayya Warfi; Eko Budi Susatyo; Sri Haryani (Chemistry in Education, 2026)
This study aimed to develop an interactive learning medium based on Articulate Storyline 3 for thermochemistry material, as well as to determine its feasibility, effectiveness, and user response. This research was motivated by the low conceptual understanding of students regarding the abstract nature of thermochemistry and the limited use of media, which was confined to textbooks and PowerPoint at SMA Teuku Umar Semarang. The research method used was Research and Development (R&D) with the 4D model (Define, Design, Development, Disseminate ). The research subjects consisted of 25 grade XII science students for a small-scale trial and 33 grade XI science students for a large-scale trial. Data were collected through interviews, expert validation questionnaires, response questionnaires, and conceptual understanding tests (pre-test and post-test). The results showed that the learning medium was declared "highly feasible" based on material expert validation with an average score of 35.5 out of 40 and media expert validation with an average score of 59.5 out of 64. The medium's effectiveness was proven to be "effective" in enhancing conceptual understanding, as indicated by an average N-Gain score of 0.834 (high category). Furthermore, the medium received a "very good" response from students with an average score of 3.82 and a "good" response from the teacher with a score of 3.00. It is concluded that the interactive learning medium based on Articulate Storyline 3 is feasible, effective, and received positive responses for use in the high school chemistry learning process.